Does education raise productivity and wages equally? The moderating role of age and gender - Stephan Kampelmann; François Rycx; Yves Saks; Ilan Tojerow (IZA Journal of Labor Economics, 2018)
We estimate the impact of education on productivity, wage costs and productivity-wage gaps (i.e. profits) using Belgian linked panel data. Findings highlight that educational credentials have a stronger impact on productivity than on wage costs. Firms' profitability is found to rise when lower educated workers are substituted by higher educated ones. This effect is found to be more pronounced among younger workers and women. Findings thus suggest that the productivity to wage cost ratio of low-educated workers is detrimental to their employability, especially when young or female. They also support the existence of a glass ceiling on women's career development.
Keywords: C33; I21; J24; J31; 330; Education; Labour costs; Productivity; Gender; Age Linked panel data